On an application of the Crum-Krein transformations - Khristov, Evgeni; Mishev, Jordan (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
Using the Crum-Krein transformations, a simple algorithm is constructed, which reduces the problem of expansion in products of solutions of two radial Schrodinger equations when one of them has purely continuous spectrum and the other one has in addition one descreet eigenvalue to the simplest case when the both equations have purely continuous spectra.